Correctness Criterion for Calculating Ion Trajectories in Edge Magnetic Fields of Static Sector Mass Analyzers - Sachenko, V. D.; Antonov, A. S. (Journal of analytical chemistry (New York, N.Y.), 2021)
An objective criterion of the computation accuracy of ion trajectories aberration components in magnetic edge fields of static mass analyzers is derived.